(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital transformation is similar to magic wand. However, human intelligence can’t be overtaken by technology. We are basically working on creating tech skilled workforce. Best organizations primarily focus on culture to come in tune with technology. They avoid sweeping changes and ham-handed approach. The transition requires more time and energy. Digital transformation is happening but in siloed manner. If digital transformation is equipped with the data sharing and data culture we can achieve the true potential immersed in it. Digital transformation is gateway to success.